Effects of mechanical box pruning intensity on bud development, vegetative growth, and yield components on cv. Cabernet-Sauvignon in Mendoza, Argentina - Barcia Poblete, Fernando Andres; Prieto, Jorge Alejandro; Trentacoste, Eduardo Rafael (International Viticulture and Enology Society, 2024)
Mechanised winter pruning is increasingly being used to reduce the high costs of manual pruning. Mechanised pruning is non-selective, and for its optimal application, the definition of pruning intensity is necessary to achieve the target yield and grape quality. Our objectives were to evaluate the effects of three intensities of mechanical box pruning compared to a manual pruning treatment on spur length, the number of retained buds, budburst, shoot growth, and development; yield components and berry composition, and vine balance. Treatments corresponded to three mechanical pruning intensities leading to different bud loads at the beginning of the experiment by pruning at different distances from the cordon (i.e., box size): MP1 (1 cm height × 7 cm width), MP2 (14 cm × 14 cm), and MP3 (21 cm × 21 cm). MP2 treatment was also compared to a traditional manual pruning treatment (SP) that was pruned to the same bud/plant in the first season. In the first season, MP2 retained the same bud/plant as SP, but in the second and third seasons, MP2 retained 88 % and 100 % more buds/plant than SP, respectively. Accordingly, MP2 and SP showed no difference in yields in the first season, but in the second season, MP2 showed a 39 % higher yield than SP. Regarding the intensity of mechanical pruning, after treatments were applied, the number of retained buds increased as box size increased. Treatments modified the length of spurs, budburst percentage and their pattern. In the first season, the yield on the highest box (MP3) was four times higher than the smallest box (MP1), but they showed similar yields in the second season. The intensity of mechanical box pruning, applied after two seasons, generated regulatory and compensation mechanisms (i.e., lower budburst and cluster weight), leading to similar yields independently of the pruning intensity. Our results show that (i) after two seasons, mechanical pruning was more productive than manual pruning, and (ii) mechanical pruning intensity had a marked influence on yield only during the first year of application, while some compensation mechanisms among yield components equilibrate yield afterwards.